PRUNING OPERATION IN URBAN TREES USING TWO AERIAL WORK PLATFORMS - Cabral, Oscar Manuel de Jesús Vera; Rodrigues, Carla Krulikowski; Barúa Acosta, Hugo Armando; Acosta, Juan José Bonnin; Lopes, Eduardo da Silva (Floresta, 2021)
The need to reduce accident risks and physical effort of workers in urban tree pruning operations promotes a search for technologies with less execution cost. In this context, the aim of this study was to evaluate the operational performance of urban tree pruning with two aerial work platforms conducted in trees under public and private domain in Greater Asunción, Paraguay. The aerial work platforms evaluated were an articulated boom lift and truck mounted boom lift in three working envelopes levels. Work cycle times, operational efficiency, fuel consumption, and operating costs were determined through a time and motion study. Sampling consisted of 78 trees in which the mean values between the working envelope levels were compared by the Tukey test (α = 0.05). The longest consumed work cycle time was in pruning without machine base motion with a mean operational efficiency of 86.2 and 76.8% in the articulated boom lift and truck mounted boom lift, respectively. Fuel consumption increased with working envelope levels, and it was the highest in the truck mounted boom lift, from 7.33 to 9.33 L h-1 of diesel fuel, at USD 18.93 per hour. Therefore, the articulated boom lift and truck mounted boom lift evaluated in urban tree pruning presented different operating costs which increased with the highest range of motion level. The main reason for this was the engine operation intensification and energy expenditures required by the machines’ hydraulic system, especially in the truck mounted boom lift.